Influence of remote education on consumer value of university education. Issue 3 (8th April 2019) - Bogoviz, Aleksei V.; Lobova, Svetlana; Ragulina, Julia; Alekseev, Alexander
Abstract : Purpose: The purpose of this paper is to study the influence of remote education on the consumer value of university education by the example of modern Russia. Design/methodology/approach: The authors determine the consumer value of university education in modern Russia in the conditions of the availability of predominantly traditional education; determine socio-economic problems that are caused by the low consumer value of university education in modern Russia; determine the potential of remote education in the increase of the consumer value of university education; and develop recommendations for the increase of the consumer value of university education in modern Russia through the development of remote education. Findings: It is concluded that traditional university education is dominating in Russia. It is standardized and does not allow for the full consideration of individual capabilities and needs of each separate student, which causes the low consumer value of university education. The limitation of traditional and remote education, caused by the fact that educational services in each form are provided by completely different universities, hinders the development of the potential of remote education in stimulating the increase of the consumer value of university education. Originality/value: In order to solve this problem, it is recommended to unify traditional and remote education within the diversification of the forms of the provision of educational services by modern Russian universities. For that, a conceptual model for increasing the consumer value of university education in modern Russia through the development of remote education is presented. This model focuses on applicant and students with their individual capabilities and needs and universities with their material and technical, intellectual, marketing and other resources. At that, the educational form goes to the background, being not a self-goal but a method of its achievement – the provision of the high consumer value of university education.